Attenuating Pain With the Past: Nostalgia Reduces Physical Pain - Kersten, Mike; Swets, Julie A.; Cox, Cathy R.; Kusumi, Takashi; Nishihata, Kazushi; Watanabe, Tomoya (Frontiers in Psychology, 2020)
Previous work has found that nostalgia, a sentimental longing for the past, is associated with psychological, emotional, and social benefits. Recent research has demonstrated that nostalgic reflection also can improve individuals’ physical health (i.e., exercise) and reduce temperature-related pain. Building on this, two experiments examined how nostalgia counteracts the threat of physical pain. Specifically, Study 1 showed that inducing nostalgia through a writing task decreased perceived pain severity among self-reported chronic pain sufferers. Study 2, in turn, demonstrated that Japanese individuals experienced increased pain tolerance toward a pressure algometer task following thoughts of nostalgia (vs. a control prime). This work provides evidence that nostalgic reflection may serve as a psychological resource to reduce the perceived severity of physical pain.